Modelling the impact of repeat asymptomatic testing policies for staff on SARS-CoV-2 transmission potential. (21st January 2023) - Whitfield, Carl A.; Hall, Ian; ,
Abstract: Repeat asymptomatic testing in order to identify and quarantine infectious individuals has become a widely-used intervention to control SARS-CoV-2 transmission. In some workplaces, and in particular health and social care settings with vulnerable patients, regular asymptomatic testing has been deployed to staff to reduce the likelihood of workplace outbreaks. We have developed a model based on data available in the literature to predict the potential impact of repeat asymptomatic testing on SARS-CoV-2 transmission. The results highlight features that are important to consider when modelling testing interventions, including population heterogeneity of infectiousness and correlation with test-positive probability, as well as adherence behaviours in response to policy. Furthermore, the model based on the reduction in transmission potential presented here can be used to parameterise existing epidemiological models without them having to explicitly simulate the testing process. Overall, we find that even with different model paramterisations, in theory, regular asymptomatic testing is likely to be a highly effective measure to reduce transmission in workplaces, subject to adherence. This manuscript was submitted as part of a theme issue on "Modelling COVID-19 and Preparedness for Future Pandemics". Highlights: Model of SARS-CoV-2 test sensitivity and infectiousness based on data freely available in the literature. Simple, efficient algorithm for simulating testing in a heterogeneous population. Regular lateral flow tests have a similar impact on transmission to PCR tests. Adherence behaviour is crucial to actual testing impact. Regular testing reduces the size and likelihood of outbreaks in closed populations.